Triomphes royaux dans les Entrées toulousaines des xvie et xviie siècles - Colin Debuiche (Les Cahiers de Framespa)
The Royal Entry was a favored ritual of the Monarchy from the end of Middle-Ages to the 17th century. It was an opportunity for the King to show himself in his best light and to present his sacred being to the visited City, which, in turn, was organized into a hierarchy and united by allegiance. Indeed, the town councilors also strived to defend their city’s privileges. Therefore, this rare and fleeting event was a subtle face to face expressed through a rich iconographic program. Toulouse, capital of the Languedoc region, was often visited by its sovereigns for whom ephemeral settings were conceived. During periods of religious turmoil, Royal Entries were made in 1565 for Charles IX and in 1621 for Louis XIII. These are examined here in order to evaluate the evolution of this face-off between King and city. This paper will also put into national context Toulouse’s customs. Indeed, from the end of the 16th century to mid-17th century, royal celebrations were undergoing radical transformations.